2021
DOI: 10.1002/jcp.30319
|View full text |Cite
|
Sign up to set email alerts
|

SIRT3 mitigates intervertebral disc degeneration by delaying oxidative stress‐induced senescence of nucleus pulposus cells

Abstract: Senescence of nucleus pulposus (NP) cells (NPC) is a major cause of intervertebral disc degeneration (IVDD), so delay NPC senescence may be beneficial for mitigating IVDD. We studied the effect and mechanism of silent information regulator 2 homolog 3 (SIRT3) on NPC senescence in vivo and in vitro. First, we observed SIRT3 expression in normal and degenerated NPC with immunohistochemical and immunofluorescence staining. Second, using SIRT3 lentivirus transfection, reactive oxygen species probe, senescence-asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 56 publications
3
44
0
Order By: Relevance
“…The overexpression of ROS seriously harms cell homeostasis and leads to the accumulation of damaged DNA and dysfunctional mitochondria, especially in degenerative diseases with weak antioxidant defense mechanisms (Grishko et al, 2009). Continuous release of ROS leads to oxidative stress, creating cell apoptosis and premature senescence, and ultimately leading to cell death (Lin et al, 2021). In this study, TBHP was selected as an ROS donor to create an oxidative stress condition in vitro study.…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of ROS seriously harms cell homeostasis and leads to the accumulation of damaged DNA and dysfunctional mitochondria, especially in degenerative diseases with weak antioxidant defense mechanisms (Grishko et al, 2009). Continuous release of ROS leads to oxidative stress, creating cell apoptosis and premature senescence, and ultimately leading to cell death (Lin et al, 2021). In this study, TBHP was selected as an ROS donor to create an oxidative stress condition in vitro study.…”
Section: Discussionmentioning
confidence: 99%
“…H 2 O 2 is commonly used to induce oxidative damage in mechanistic studies of IDD[ 20 , 22 ]. The inflammation, apoptosis and senescence of NP cells and the apoptosis and senescence of NPMSCs are important pathological models for exploring IDD, which can all be induced by H 2 O 2 treatment[ 23 - 26 ]. In our previous study, we confirmed that H 2 O 2 treatment could decrease the viability of NPMSCs in a dose- and concentration-dependent manner, and a concentration of 80 μM for 6 h could be used as a suitable concentration in vitro [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Through the upregulation of mitochondrial antioxidation signals as well as the enhancement of mitochondrial dynamics and mitophagy, the activation of AMPK-PGC-1α-SIRT3 pathway suppresses mitochondrial apoptosis and senescence in rat NP cells exposed to TBHP ( Wang et al, 2018 ). AMPK-induced activation of PGC-1α-SIRT3 pathway can also inhibit the secretion of pro-inflammatory cytokines, including IL-1β and IL-6, and relieve the imbalance between the synthesis and degradation of ECM in rat NP cells stimulated by oxidative damage ( Lin et al, 2021 ). Acetyl-CoA carboxylase (ACC) is widely known as an important intermediate metabolite in fatty acid metabolism.…”
Section: Amp-activated Protein Kinase In the Pathophysiology Of Intervertebral Disc Degenerationmentioning
confidence: 99%